KONSEP FILSAFAT PENDIDIKAN MUHAMMADIYAH - Khosiah, Nur; Nurhakim, Moh; Amin, Syaiful (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
Philosophy is the mother of science, all humans are good at philosophy because they are given the advantage of thinking by Allah SWT. The aim of this research is to find out what the concept of Muhammadiyah educational philosophy is. This research uses a descriptive qualitative approach with library research methods. Which results in the conclusion that Muhammadiyah is an educational institution that has a non-political nature. The characteristic of Muhammadiyah education is the existence of Al-Islam and Muhammadiyah education at the elementary school level to the tertiary level. Muhammadiyah, with the motto "advanced Islam", has the potential to become the ideological foundation of civilization. More than just a theological or philosophical expression, it is reflected in social, political, economic and cultural practice. Muhammadiyah's educational philosophy emphasizes six main principles. This education aims to provide benefits to all of nature (rahmatan lil alamin), make the Prophet a good role model (uswatun hasanah), pay attention to the interests of the world and the hereafter, develop human potential as caliphs on earth, compete in goodness, and pay attention to science and technology.